2005
DOI: 10.1103/physrevb.71.024519
|View full text |Cite
|
Sign up to set email alerts
|

Experimental ratchet effect in superconducting films with periodic arrays of asymmetric potentials

Abstract: A vortex lattice ratchet effect has been investigated in Nb films grown on arrays of nanometric Ni triangles, which induce periodic asymmetric pinning potentials. The vortex lattice motion yields a net dc voltage when an ac driving current is applied to the sample and the vortex lattice moves through the field of asymmetric potentials. This ratchet effect is studied taking into account the array geometry, the temperature, the number of vortices per unit cell of the array, and the applied ac currents. DOI: 10.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 26 publications
6
75
0
Order By: Relevance
“…The same behavior is found in both cases ͑ac and dc driving forces͒. 6 The experimental data shown in Figs. 2 and 3 are taken in the adiabatic limit.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The same behavior is found in both cases ͑ac and dc driving forces͒. 6 The experimental data shown in Figs. 2 and 3 are taken in the adiabatic limit.…”
supporting
confidence: 64%
“…2,5 Moreover, this vortex ratchet is an adiabatic ratchet; i.e., the effect shows a nonfrequency dependence that allows us to study and mimic the vortex ratchet effect by I͑V͒ curves. 6,7 The possible transverse rectification of particles has been theoretically studied by several authors. 8,9 The transverse ratchet effect for vortices moving in arrays of triangular pinning sites was specifically studied by Reichhardt-Olson and Reichhardt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Applications to removal of trapped flux from superconductors, and to voltage rectification have been proposed [2,3,4,5,6,7]. Experimental realizations of the ratchet effect for vortices have been reported by some groups [8,9,10]. The work so far has concentrated on vortex pinning potentials resulting from periodic modulations of the film thickness or from periodic arrays of anti-dots or blind holes with asymmetric shape.…”
Section: Introductionmentioning
confidence: 99%
“…Worth a while to note that the ratchet effect is not frequency dependent in the range attainable in our experiment up to 10 kHz. Villegas et al (3) have explored this effect, recently van Vondel et al (7) has found the same behavior in superconducting Al films with array of asymmetric antidotes (holes). Both found that the vortex ratchet effect is in the adiabatic limit, but in both cases the analysis is done for n=2, (2) and n=1 We are going to study the possible adiabatic behavior when both types of vortices develop, that is vortices pinned in the Ni triangles and interstitial vortices.…”
Section: Resultsmentioning
confidence: 95%